Scaling-up agricultural technologies: Who should be targeted? - Bedi, S.M.; Azzarri, Carlo; Kotu, Bekele Hundie; Kornher, L.; Braun, Joachim von (Oxford University Press, 2022)
The effects of agricultural technology adoption on farm performance have been studied extensively but with limited information on who should be targeted during scaling-up. We adopt the newly defined marginal treatment effect approach in examining how farmers’ resource endowment and unobserved factors influence the marginal benefits of adopting sustainable intensification (SI) practices. We estimate both the marginal and average benefits of adopting SI practices and predict which marginal farm household entrants will benefit the most at scale. Findings indicate that farmers’ resource endowment and unobserved factors affect the marginal benefits of adopting SI practices, which also influence maize yield and net returns among adopters. Finally, results imply that scaling up SI practices will favour farm household entrants associated with the lowest probability of adoption based on observed socioeconomic characteristics.